Variations of the tropical Atlantic and Pacific SSS minimum zones and their relations to the ITCZ and SPCZ rain bands (1979–2009). Issue 7 (23rd July 2015) - Tchilibou, M.; Delcroix, T.; Alory, G.; Arnault, S.; Reverdin, G.
Abstract This study focuses on the time‐space variability of the low Sea Surface Salinity (SSS) waters extending zonally within 2°N–12°N in the Atlantic and Pacific and within 6°S–16°S in the western third of the Pacific. The analysis is based on a combination of in situ SSS observations collected in the last three decades from voluntary observing ships, TAO/TRITON and PIRATA moorings, Argo floats, and (few) CTD profiles. The mean latitudes of the Atlantic and Pacific low SSS waters appear 1°–3° further poleward than the Evaporation minus Precipitation (E‐P) minima linked to the Inter Tropical Convergence Zones (ITCZ) and South Pacific Convergence Zone (SPCZ). At the seasonal time scale, the E‐P minima migrate poleward in summer hemispheres, leading the migration of the SSS minima by 2–3 months in the Atlantic ITCZ, Pacific SPCZ, and in the eastern part of the Pacific ITCZ. On the other hand, the seasonal displacements of E‐P and SSS minima are in antiphase in the central and western parts of the Pacific ITCZ. At the interannual time scale, the E‐P and SSS minima migrate poleward during La Nina events in the Pacific and during the positive phase of the Atlantic Meridional Dipole (AMD) in the Atlantic (and vice versa during El Nino and the negative phase of the AMD). We further document long‐term (1979–2009) meridional migrations of the E‐P and SSS minima, especially in the SPCZ region, and discuss whether or not they are consistent with documented SST and wind stress trends.